Rethinking Immersion in Digital Heritage: A Technology–Narrative–Emotion Framework for Cross-Media Cultural Communication - Wu, Yifan (Art and Society, 2025)
In the context of digitalization and media convergence, cultural heritage dissemination is being reshaped by immersive technologies such as VR, AR, AI-driven narratives, and digital twins. While existing research has explored visualization, interface design, and digital preservation methods, the underlying mechanism through which immersion is generated—particularly the dynamic interaction of technological structures, narrative organization, and emotional engagement—remains insufficiently theorized. To address this gap, this study examines immersive digital heritage as its core research object and employs a theoretical and conceptual analysis approach. Through the synthesis and integration of interdisciplinary scholarship, the study proposes a “technology–narrative–emotion” analytical framework to reveal how immersive experience emerges from the interplay between technical affordances, narrative restructuring, and users’ affective responses. The findings demonstrate that digital heritage immersion is not produced by any single factor but is constructed through continuous negotiation among technological mediation, narrative meaning-making, and emotional resonance. This process transforms cultural heritage from a static representation into a dynamic field of experiential interpretation. However, the analysis also identifies several risks: strengthened narrative authority induced by technological control, the hyperreal effect produced by high-fidelity visual restoration, and the potential reduction of complex historical memory into short-lived emotional peaks.